Temporal and demographic variations in attendance at accident and emergency departments. Issue 6 (1st November 2002) - Downing, A; Wilson, R
Abstract : Objectives: Little has been reported of the demographic and temporal variations in accident and emergency (A&E) attendances despite the importance of this information in planning services. The purpose of this paper to is to explore the variations in attendance patterns across the West Midlands region of the NHS. Methods: The data were obtained from the A&E minimum dataset from a sample of 13 hospitals. Arrival dates and times, age, and sex of all patients attending A&E in the year from 1 April 1999 to 31 March 2000 were analysed to look at the pattern of attendance by hour, day and month, age, and sex. Results: No differences were found in attendance patterns in respect to sex. Attendances by children under 15 years peaked in the evening between 18:00 and 19:59. In contrast, peak attendance in those over 15 years was between 09:00 and 11:59. The percentage of "out of hours" attendances in this dataset was highest in the under 1 age group (58.5%), the 15–24 age group (57.1%), and the 25–44 age group (54.6%). The highest proportion of patients attended A&E on a Monday, while the percentage of weekend attendances decreased with age. In children aged 1–14 years there were more attendances in summer than winter. In those aged under 1 and over 65 there was a winter peak with December having the most attendances. Conclusions: No sex differences were found in the temporal attendance patterns at A&E. However, many differences were found in the attendance of different age groups. These differences are of great importance in the planning of services, and further research is required to explain the reasons behind these variations.